Surfactant Protein D in Chornic Obstructive Pulmonary Disease (COPD) - Moreno, Dolores; Garcia, Alexis; Lema, Diego; B. De Sanctis, Juan (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2014)
In the recent years, a large number of potential biomarkers for Chronic Obstructive Pulmonary Disease (COPD) have been described. One of the important biomarkers is Surfactant Protein D (SPD) since serum SPD levels have been associated with lung function or health status in patients with severe COPD. Several interesting evidences of the protein and gene polymorphisms have been described. The present review highlights the current literature, recent patents and, future prospects of this important collection.
Keywords: exacerbations